2020
DOI: 10.1017/cjn.2020.37
|View full text |Cite
|
Sign up to set email alerts
|

A New Inexpensive Simulation Model for Ultrasound Assessment of Optic Nerve Sheath Diameter

Abstract: ABSTRACT:Background:Sonographic measurement of optic nerve sheath diameter (ONSD) is becoming increasingly accepted as a diagnostic modality to detect elevations in intracranial pressure. As this technique becomes more widespread, methods to address the inherent operator-dependent nature of this modality will need to be developed. We propose a novel low-cost model to accurately simulate sonographic ONSD measurement for purposes of training and assessment.Methods:We designed models composed of medical tubing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We used tubing of various diameters from medical supplies made out of a variety of different plastics. However, when we analyzed and validated these models previously, we found that no model appeared to stand out as a poor performer ( 23 ). Again, in our current study, none of the models appeared to stand out as being a particular outlier, other than the smallest tube, which was composed of the same materials as many of the larger tubes.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We used tubing of various diameters from medical supplies made out of a variety of different plastics. However, when we analyzed and validated these models previously, we found that no model appeared to stand out as a poor performer ( 23 ). Again, in our current study, none of the models appeared to stand out as being a particular outlier, other than the smallest tube, which was composed of the same materials as many of the larger tubes.…”
Section: Discussionmentioning
confidence: 92%
“…Measurements were made using a simulation model of the ONS as published previously ( 23 ) ( Figure 1 ). In brief, medical tubing of various diameters was cut to 1 cm in length, encased in an opaque gelatin-psyllium powder matrix, and placed in Styrofoam TM coffee cups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation